2005
DOI: 10.1590/s1516-35982005000600038
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do fornecimento de monensina e óleo de soja na dieta sobre o desempenho de vacas leiteiras na fase inicial da lactação

Abstract: RESUMO -Avaliou-se o efeito do fornecimento de monensina e óleo de soja na dieta sobre o desempenho de vacas leiteiras na fase inicial de lactação. Foram utilizadas 16 vacas multíparas 7/8 Holandês Gir, com 30 dias em lactação, em um delineamento em blocos ao acaso, em esquema fatorial. O período experimental teve duração de 84 dias, divididos em três fases: I -5ª à 8ª; II -9ª à 12ª; III -13ª à 16ª semana de lactação. Os tratamentos foram denominados: CT: dieta controle -sem óleo e sem monensina; MN: dieta sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
3
0
12
Order By: Relevance
“…Gallardo et al (2005) also reported positive effect by adding monensin, which increased milk yield by 4.0% in comparison to the control diet (27.7 vs. 26.6 kg/day, respectively). Eifert et al (2005) did not find any effect for milk yield when comparing the experimental diets, although the diet with monensin resulted in a higher value for milk yield (3.0%), in comparison with the control diet (26.5 vs. 26.6 kg/day, respectively). Similarly, Ramanzin et al (1997); Zahra et al (2006) and Martineau et al (2007) did not observe effect of sodium monensin addition on milk yield of lactating cows.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Gallardo et al (2005) also reported positive effect by adding monensin, which increased milk yield by 4.0% in comparison to the control diet (27.7 vs. 26.6 kg/day, respectively). Eifert et al (2005) did not find any effect for milk yield when comparing the experimental diets, although the diet with monensin resulted in a higher value for milk yield (3.0%), in comparison with the control diet (26.5 vs. 26.6 kg/day, respectively). Similarly, Ramanzin et al (1997); Zahra et al (2006) and Martineau et al (2007) did not observe effect of sodium monensin addition on milk yield of lactating cows.…”
Section: Resultsmentioning
confidence: 65%
“…In the study by Eifert et al (2005), using dose of 33 mg/ kg DM of sodium monensin, dry matter intake was reduced by only 1.4%, in comparison to the control diet. The results obtained in this research are similar to the ones verified by the cited authors.…”
Section: Resultsmentioning
confidence: 89%
“…Do mesmo modo, Silva (1997) encontrou menor produção de leite e produção de leite corrigida para 3,5% de gordura quando forneceram 30% de grão de soja cru moído no concentrado. Respostas negativas na produção de leite de vacas em lactação sob suplementação lipídica também foram observadas por Eifert et al (2005). As menores produções de leite corrigidas podem ser explicadas pelo aumento Figura 1 -Produção de leite (kg/dia) e produção de leite corrigida para 4% de gordura (kg/dia) de búfalas alimentadas com dietas com diferentes fontes de lipídeo.…”
Section: Resultsunclassified
“…A diminuição no consumo de MS em vacas lactantes ocasionada pelo fornecimento de óleos vegetais tem sido observada, mas sua causa ainda não está bem estabelecida (Eifert et al, 2005). Freqüentemente, a explicação é relacionada à interferência dos lipídios insaturados sobre a atividade das bactérias Gram-positivas, principais envolvidas na fermentação da fibra (Cant et al, 1997).…”
Section: Em Vacasunclassified